NÄsikh-MansÅ«kh dalam Al-Qurâ€™Än - Said, Mohammad Umar (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
Islam must be able to exist in all situations and conditions, Al Qur'an as the main source is expected to have its existence especially in facilitating the benefit of Muslims. Because the benefit and needs of one community to another have differences, then the need for the concept of abrogation becomes one of the media and methods in weighing a benefit that implies the emergence of relevant new laws to be applied. This paper tries to unravel the basic concepts of abrogation (Naskh) and the domain of its work in the area of Islamic jurisprudence. with descriptive-analytical study, the result is that the concept of abrogation must indeed exist in the minds of every mujtahid in formulating a legal solution.